Transformasi Kebijakan Maritim dalam Era Digital: Peran Teknologi dalam Meningkatkan Efektivitas dan Keamanan Lautan di Indonesia - Deanto, Muhammad Arrafi Rizcy; Marzaman, Atika Puspita (Journal of International and Local Studies, 2024)
Indonesia's maritime potential holds a significant position in the country's economy, considering Indonesia's status as an archipelagic country with several ports and sea routes which have a strategic position because Indonesia is located between two continents and two oceans, namely Asia and Australia Continents, and, Indian and the Pacific Oceans. As much as 40% of world trade routes also pass through Indonesia. However, the challenge faced by Indonesia in utilizing its potential is that maritime effectiveness and security are still low. Therefore, the transformation of maritime policy in the digital era is important to increase maritime effectiveness and security in Indonesia. Transforming maritime policy in the digital era can help improve port connectivity, increase maritime supply chain efficiency, and strengthen maritime security systems. This research will use a mixed methodology that includes literature analysis and policy analysis to explain the role of technology in increasing maritime effectiveness and security in Indonesia in the digital era. This writing concluded that the transformation of maritime policy in the digital era can have a significant impact on real-world security and cyber security. However, there are obstacles that need to be overcome so that the use of technology in maritime policy can be carried out effectively and efficiently. Therefore, more serious, and integrated efforts are needed from the government and society to overcome these obstacles and ensure that the transformation of maritime policy in the digital era can provide optimal benefits for the security and defense of maritime areas as well as cyber security in Indonesia.